Monday

April 21, 2014

April 21, 2014

Posted by **faith** on Thursday, July 19, 2012 at 10:08am.

- math -
**Bosnian**, Thursday, July 19, 2012 at 11:03amWhat is your question?

- math -
**Henry**, Friday, July 20, 2012 at 3:37pm(2x-3y)(2y+3x).

1. Multiply 2x by each term in the 2nd

parenthesis.

2. Multiply -3y by each term in the 2nd

parenthesis.

3. Combine like-terms.

(2x-3y)(2y+3x) =

4xy + 6x^2 - 6y^2 - 9xy =

6x^2 - 5xy - 6y^2.

**Related Questions**

Math help - How do you do these questions, I have all my steps done until the ...

Math - How do you do these questions, I have all my steps until the last one: 2x...

Math - How do you do these questions, I have all my steps done until the last ...

Math Ms Sue check - How do you do these questions, I have all my steps done ...

derivative - I am finding the second derivative of (x^2)(y^3) = 1 2x(y^3) + (x^2...

Please any math helper!! - How do you do these questions, I have all my steps ...

Math - Which line below is parallel to y=-2/3x+5? a. 2x-3y=6 b. 2x+3y=6 c. 3x-2y...

algebra 1 - Why Does A Poor Man Drink Coffee? use the and y-intercept to graph ...

Math - 2x-3y=6 I did +3y 2x=6+3y 1/2 to both sides(2x=3y/2+6) x=3/2y+6 or does ...

correction of math - rewrite the equation 2x-3y= -6 as a function of x. My ...